Pengaruh Penambahan Ampas Tahu Dan Keong Mas (Pomacea canaliculata) Pada Ratro Pellet Komersil Terhadap Pertumbuhan Ikan Lele (Clarias gariepinus) - Raodatul Jannah; Nanda Diniarti; Dewi Putri Lestari (Otus Education: Jurnal Biologi dan Pendidikan Biologi, 2024)
The need for fish food is one of the essentials that can determine the level of success of the fish growth and development process. This research aims to analyze the effect of a combination of pelleted feed and animal feed on the growth and survival of catfish (Clarias gariepinus). The research was carried out for 60 days, at the Mataram University fish production and reproduction laboratory using an experimental method with a completely randomized design (CRD) consisting of 5 treatments and 3 replications, namely: A: 100% commercial feed (control), B: Fish Pellets 50% + Golden Snail 25% + Tofu Dregs 25%, C: Fish Pellets 25% + Golden Snails 50% + Tofu Dregs 25, D: Fish Pellets 25% + Golden Snails 25% + Tofu Dregs 50% and E: Fish Pellets 34% + Keong Mas 33% + Tofu dregs 33%. Test parameters include absolute weight, absolute length, specific weight growth rate, specific length growth rate, feed conversion ratio, feed utilization efficiency and survival and water quality. Data were analyzed using Analysis of Variance (ANOVA) and continued with the Duncan test. The results of this study showed that the best growth and survival of catfish was found in the treatment with 34% commercial feed, 33% golden snails and 33% tofu dregs (P4) with an absolute weight of 15.09 g, an absolute length of 7.05 cm , the specific weight growth rate was 3.86%/day, the length growth rate was 1.3%/day, the feed conversion ratio was 1.18, the feed efficiency rate was 85.91% and the survival rate was 73.33%. The proximate test results showed that the highest content was found in the treatment given 25% commercial feed, 50% golden snails and 25% tofu dregs (P2) with a dry content of 36.39%, crude fiber 10.86% and crude protein 31.48%.